On the CP Violation Phase in a Neutrino Mixing Model with an A4 Flavor Symmetry - Van, Phi Quang; Van, Nguyen Thi Hong (Communications in Physics, 2016)
Neutrino masses and mixing in an extended standard model acquiring an A4 flavour symmetry are considered. The corresponding three-neutrino mixing matrix obtained via a pertur- bative method allows us to determine the Dirac CP violation phase (δ_{CP}) as a function of the mixing angles (θ_{12}, θ_{23}, θ_{13}). Then, numerical values and distributions of δ_{CP} are given. The latter values are quite close to the global fits of the experimental data for both the normal ordering and inverse ordering of the neutrino masses.